The Effect Of Learning Methods And Teaching Media On Learning Motivation Of Business Education Students - Laila Azkiya Ulinnuha; Aulia Salwa Ursila; Nabila Febrianti; Salwa Aulia Ruman; Nadila Nur Hamidah (International Journal of Technology and Education Research, 2025)
This study aims to analyze the influence of learning methods and teaching media on the learning motivation of Business Education students, class of 2023, at Surabaya State University in the Mathematics and Economics course. The background of this study is the decline in student learning motivation after the COVID-19 pandemic, where 48% of students in Indonesia have low learning motivation. This study uses a quantitative approach with a multiple linear regression method. The study population was all 145 Business Education students, class of 2023, with a sample of 106 students selected using a simple random sampling technique. Data collection was carried out through a questionnaire with a Likert scale (1-5). The results showed that learning methods partially did not have a significant effect on student learning motivation (T count 0.894 < T table 1.659; sig. 0.373 > 0.05). In contrast, teaching media had a significant effect on student learning motivation (T count 5.077 > T table 1.659; sig. 0.000 < 0.05). Simultaneous tests show that learning methods and teaching media together have a significant effect on student learning motivation (F count 35.345 > F table 3.08; sig. 0.000 < 0.05). This study provides important implications for the development of more effective learning strategies, especially in optimizing the use of teaching media to increase student learning motivation in the digital era. It is recommended that lecturers pay more attention to the variety and creativity of learning media used in the Mathematics Economics lecture process.